Transformasi Manajemen Sumber Daya Manusia Di Era Digitalisasi: Inovasi Dan Tantangan dalam Menghadapi Kecerdasan Buatan - Ahmad Gunawan; Santi Aprilianti; Nur Syifa Syaharany (CV. ITTC INDONESIA, 2025)
The transformation of human resource management (HR) in the era of digitalization has become the main focus in facing the challenges and opportunities presented by artificial intelligence (AI). This article examines the innovations offered by AI in HR practices, including automating recruitment processes, analyzing employee data, and improving employee experience through personalization technologies. On the other hand, the study also identifies emerging challenges, such as the need to improve HR skills, maintain human interaction in an increasingly automated environment, and address ethical issues related to the use of AI. Through a case study approach and literature analysis, this article provides recommendations for organizations to effectively integrate AI in HR strategies, while maintaining human values. These findings aim to help HR leaders formulate sustainable adaptive strategies in the midst of rapid changes in the world of work.